THE USE OF PQ4R METHODS AS AN EFFORT TO IMPROVE STUDENT ACHIEVEMENT IN EXPLANATION TEXT MATERIAL ON STUDENTS OF XII IPA-1 SMAN I BEBER CIREBON ACADEMIC YEAR 2015/2016 - Ine Silviyanti (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2017)
Initial experience can be built through reading activities. With this activity learners will have a stock of knowledge. One method that can be developed for effective reading is PQ4R Robert M. Gagne (in J.J.J Hasibuan and Moedjiono, 1986: 5). The aim of this study:1) To know the activity of students with cooperative learning method PQ4R 2) To know Student learning outcomes with cooperative learning method PQ4R. The subject of the recipients of the action is the students of class XII IPA-1 SMAN I Beber, with the number of students 40 people with details of 19 male students and 21 female students. Data obtained through observation, field notes and review the validity of data examined and analyzed descriptively qualitative and quantitative. The results of Class Action Research: can develop student creativity, understanding the effective learning through the use of PQ4R method can change the teacher's habits from researcher to facilitator and can improve student learning outcomes in a positive direction. The result of research by applying PQ4R method obtained average value of student achievement average value from Pre Cycles stage equal to (69,8) with perfection percentage (17,5%). the average cycle of test II (81.5) with the percentage of completeness (80%) and the final test result of the whole cycle (76.8) with the percentage of completeness (42.5%), sub sumative) on average (86.3) with a percentage of mastery of (100%). Non-test results showed a change in the attitude and behavior of students in the learning process. sThe activities and skills of student cooperation are getting better, along with the development of students' understanding ability on learning English. Thus it can be concluded that learning English through PQ4R method on Explanation Text material, can improve students’ achievement class XII IPA-1 SMA N I Beber Cirebon. Key words: PQ4R Method, Learning Achievement